Psychospołeczne uwarunkowania oceny znaczenia własnej choroby przez osoby przewlekle chore - Joanna Furmańska, Joanna Furmańska; Rzepa, Teresa; Pietrzak-Nowacka, Maria; Koziarska, Dorota (Człowiek i Społeczeństwo, 2018)
The literature on the subject identifies chronic disease as a stressor which imposes new adaptive tasks on patients and requires them to change their lifestyle. Therefore, the issues of disease assessment and adaptation to illness, based on individual knowledge of the disease and subjective appraisal of its influence on day-to-day functioning, are becoming increasingly important. In the present article, the appraisal of disease significance is to be understood as a dynamic effect of subjective assessment of one’s own life situation due to chronic disease. The aim of the analysis was validation of the relationship between the basic sociodemographic factors and the appraisal of the significance of a chronic disease among patients with RRMS and diabetes type 2, as well as verification whether these two diseases show any differences in terms of appraisal of their significance in opinion of the patients. In order to verify the hypotheses, The Disease-Related Appraisals Scale, and original scorecard designed to obtain sociodemographic data were used. The analysis was conducted on 118 patients with RRMS and 61 patients with diabetes type 2. The results show a statistically significant relationship between education level and the appraisal of disease significance considered as benefit and injustice among the two groups of patients. Additionally, in the group of patients with diabetes type 2, the aforementioned relationship was also found for appraisal of disease significance considered as a threat. Moreover, it was found that the analysed groups show significant differences in terms of recognition of the disease as an obstacle/loss. Diagnostic assessment of disease significance sets the direction and methods of therapeutic intervention provided, with the primary aim of improving the quality of life of patients suffering from a chronic disease.